Modeling net ecosystem carbon balance and loss in coastal wetlands exposed to sea‐level rise and saltwater intrusion. Issue 8 (12th August 2022) - Ishtiaq, Khandker S.; Troxler, Tiffany G.; Lamb‐Wotton, Lukas; Wilson, Benjamin J.; Charles, Sean P.; Davis, Stephen E.; Kominoski, John S.; Rudnick, David T.; Sklar, Fred H.
Abstract: Coastal wetlands are globally important stores of carbon (C). However, accelerated sea‐level rise (SLR), increased saltwater intrusion, and modified freshwater discharge can contribute to the collapse of peat marshes, converting coastal peatlands into open water. Applying results from multiple experiments from sawgrass ( Cladium jamaicense )‐dominated freshwater and brackish water marshes in the Florida Coastal Everglades, we developed a system‐level mechanistic peat elevation model (EvPEM). We applied the model to simulate net ecosystem C balance (NECB) and peat elevation in response to elevated salinity under inundation and drought exposure. Using a mass C balance approach, we estimated net gain in C and corresponding export of aquatic fluxes ( F AQ $$ F_{AQ} $$ ) in the freshwater marsh under ambient conditions (NECB = 1119 ± 229 gC m −2 year −1 ; F AQ = 317 ± 186 gC m −2 year −1 ). In contrast, the brackish water marsh exhibited substantial peat loss and aquatic C export with ambient (NECB = −366 ± 15 gC m −2 year −1 ; F AQ = 311 ± 30 gC m −2 year −1 ) and elevated salinity (NECB = −594 ± 94 gC m −2 year −1 ; F AQ = 729 ± 142 gC m −2 year −1 ) under extended exposed conditions. Further, mass balance suggests a considerable decline in soil C and corresponding elevation loss with elevated salinity and seasonal dry‐down. Applying EvPEM, we developed critical marsh net primary productivity (NPP) thresholds as a function of salinity to simulate accumulating, steady‐state, and collapsing peat elevations. The optimization showed that ~150–1070 gC m −2 year −1 NPP could support a stable peat elevation (elevation change ≈ SLR), with the corresponding salinity ranging from 1 to 20 ppt under increasing inundation levels. The C budgeting and modeling illustrate the impacts of saltwater intrusion, inundation, and seasonal dry‐down and reduce uncertainties in understanding the fate of coastal peat wetlands with SLR and freshwater restoration. The modeling results provide management targets for hydrologic restoration based on the ecological conditions needed to reduce the vulnerability of the Everglades' peat marshes to collapse. The approach can be extended to other coastal peatlands to quantify C loss and improve understanding of the influence of the biological controls on wetland C storage changes for coastal management.